Gas‐phase reactions of alcohols with hexamethylene triperoxide diamine (HMTD) under atmospheric pressure chemical ionization conditions. (15th January 2015) - Colizza, Kevin; Porter, Matthew; Smith, James L.; Oxley, Jimmie C.
<x xml:space="preserve">Abstract</x> RATIONALE Hexamethylene triperoxide diamine (HMTD) is a sensitive peroxide explosive first synthesized in 1885. HMTD exhibits an unusual gas‐phase phenomenon in the presence of alcohols that has been previously observed, but incorrectly resolved. We are attempting to determine this specific mechanism. METHODS We used positive ion mode atmospheric pressure chemical ionization (APCI) as the interface to the mass spectrometer. HMTD was infused with various solvents including 18O‐ and 2H‐labeled methanol in order to determine gas‐phase reaction mechanisms. RESULTS Based on these labeled experiments, it was determined that, under APCI conditions, the alcohol oxygen attacks a methylene carbon of HMTD and releases H2O2. This was attempted with nine different alcohols and, in each case, the alcohol is fully incorporated into the molecule with the peroxide release. A mechanism for this reaction has been proposed. CONCLUSIONS This work appears to have confirmed the gas‐phase reaction mechanism of HMTD with alcohols. As we continue efforts to characterize this unusual molecule, the information may prove useful in determining formation and degradation mechanism(s). In addition, this property of HMTD may find use in other fields of science. Copyright © 2014 John Wiley & Sons, Ltd.